What drives changes in the virulence and antibiotic resistance of Vibrio harveyi in the South China Sea? - Yiqin Deng; Liwen Xu; Songlin Liu; Qian Wang; Zhixun Guo; Chang Chen; Juan Feng (Journal of Fish Diseases, 2020)
To understand the driving environmental factors in changes of bacterial virulence and antibiotic resistance, we determined the prevalence, antibiotic resistance and antibiotic resistance and virulence genes of Vibrio harveyi isolated from diseased marine fish in south coastal China. We isolated 2, 52 and 53 V. harveyi strains from Fujian, Hainan and Guangdong, respectively, and identified them by multilocus sequence analysis of 16S rRNA‐ toxR Vh ‐ rctB . Nine typical virulence genes were represented at a higher average in Hainan (7.39 ± 0.24) than in Guangdong (6.91 ± 0.28). Five atypical virulence genes were detected in some isolates. In particular, flaC and vvh were detected in more than 60% of isolates. Their average number was significantly higher in Hainan (2.30 ± 0.20) than in Guangdong (1.70 ± 0.10). Multidrug resistance was widespread with an average resistance to 4.57 ± 0.18 of 15 antibiotics. Both the average number of antibiotic resistance and antibiotic resistance genes were higher in Hainan (5.25 ± 0.27 and 1.11 ± 0.15, respectively) than in Guangdong (3.87 ± 0.21 and 0.75 ± 0.10, respectively). This study demonstrated that there were more virulence genes and greater drug resistance in Hainan than in Guangdong, suggesting that warmer temperature and antibiotics pollutants probably enhance antibiotic resistance and bacterial infection.